DETERMINAN AGRESIVITAS PAJAK PADA PERUSAHAAN MAKANAN & MINUMAN DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Eliana, Eliana; Ivana, Farah; Kesuma, Indra; Mawardi, Mawardi; Zahra, Afifah (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study analyzes the influence of profitability, leverage, liquidity, and capital intensity on tax aggressiveness in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. With a quantitative approach, secondary data was taken from the annual financial statements of 12 selected companies through purposive sampling. Multiple regression analysis used SPSS 29 to test the influence simultaneously and partially, after going through the classical assumption test (normality, multicollinearity, heteroscedasticity, and autocorrelation). The results showed that simultaneously, the four variables had a significant effect on tax aggressiveness (F calculated = 4.244 > F table = 2.540; *p* = 0.005), with a contribution of 23%, while 77% was influenced by other factors. Partially, only leverage had a positive effect (T count = 3.720; *p* = 0.001), while profitability, liquidity, and capital intensity were insignificant. These findings indicate that debt pressure (leverage) is the main driver of tax aggressiveness, while other factors such as profitability and asset structure have no significant influence. This study enriches empirical evidence regarding the determinants of tax aggressiveness in Indonesia's manufacturing sector